2015
DOI: 10.1002/art.39043
|View full text |Cite
|
Sign up to set email alerts
|

The Somatosensory Link in Fibromyalgia: Functional Connectivity of the Primary Somatosensory Cortex Is Altered by Sustained Pain and Is Associated With Clinical/Autonomic Dysfunction

Abstract: Objective Fibromyalgia (FM) is a chronic functional pain syndrome characterized by widespread pain, significant pain catastrophizing, sympathovagal dysfunction, and amplified temporal summation for evoked pain. While several studies have found altered resting brain connectivity in FM, studies have not specifically probed the somatosensory system, and its role in both somatic and non-somatic FM symptomatology. Our objective was to evaluate resting primary somatosensory cortex (S1) connectivity, and explore how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
157
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 53 publications
10
157
0
3
Order By: Relevance
“…In fact, a recent neuroimaging meta-analysis noted S1 as part of a network of brain regions regulating autonomic, particularly sympathetic, outflow (Beissner et al, 2013). In addition, our recent study in patients with chronic pain found that pain-evoked increase in S1 connectivity to the anterior/middle insula cortex was associated with reduced cardiovagal modulation (Kim et al, 2015). These studies link S1 with central control of autonomic tone and future studies should explore if, for example, S1-insula connectivity is also associated with both autonomic (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…In fact, a recent neuroimaging meta-analysis noted S1 as part of a network of brain regions regulating autonomic, particularly sympathetic, outflow (Beissner et al, 2013). In addition, our recent study in patients with chronic pain found that pain-evoked increase in S1 connectivity to the anterior/middle insula cortex was associated with reduced cardiovagal modulation (Kim et al, 2015). These studies link S1 with central control of autonomic tone and future studies should explore if, for example, S1-insula connectivity is also associated with both autonomic (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…43,69,72 Furthermore, phasic as well as tonic application of a painful stimulus can produce temporal summation, 3 and both modes of application show a close correlation with psychosocial factors such as catastrophizing. 32 As in the current study, lower pressures are typically required to produce pain in FM patients compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Our moderately painful (40 of 100) prolonged cuff stimulus produced temporal summation in most patients with FM, consistent with previous studies that observed a modest increase in temporal summation in FM as a group over control subjects with stimulus matching. 43,69,72 The duration of the painful cuff stimulus we used was relatively long compared with some other measures of temporal summation, 5 for the purpose of increasing the likelihood of detecting temporal summation as well as PAS. Although there was some variability in the response to a prolonged cuff stimulus in both groups, FM patients reported increased incidence and severity of PAS compared with control subjects, similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…If advancing the understanding of FMS pathophysiology leads to new therapeutic targets and if there is progress in the design and execution of FMS clinical trials, new FDA-approved treatment options should eventually be available. Perhaps a renewed focus on gaining a greater understanding of the mechanism(s) underlying altered resting brain conductivity [35], the role of brain-derived neutrotrophic factor [36], thermoregulation [37] and T-type Ca 2+ channels [38] in FMS will also provide the impetus for new directions in drug development for FMS.…”
Section: Expert Commentarymentioning
confidence: 99%